An analysis of the purchaser's protection in terms of chapters two and three of the Alienation of Land Act 68 of 1981 - Lotz, D.J. (Dirk Johannes) (University of Pretoria, 2026)
Dissertation (LLM (Mercantile Law))--University of Pretoria, 2018.